CHALLENGES IN PARKINSON’S DISEASE MANAGEMENT IN PRIMARY CARE IN INDONESIA: A NARRATIVE REVIEW - Rahmawati, Fitriana; Mulyanto, Joko (Mandala Of Health, 2025)
Parkinson's disease (PD) is a rapidly growing neurological disorder with significant health implications, especially in low- and middle-income countries (LMICs) like Indonesia. This review analyzed the challenges and opportunities for managing PD in Indonesian primary care. The prevalence of PD in Indonesia has surged by 143% since 1990, reaching 89.91 per 100,000 people in 2019, which is likely underestimated owing to healthcare system limitations. Primary care is critical for early PD detection, although diagnostic accuracy is a concern. Enhancing the primary care capacity for early identification is essential through specialized training, telemedicine, and PD-specific assessment tools. Continuous monitoring of medication adherence, treatment efficacy, and symptom progression is vital for its effective management. Integrating palliative care principles and supporting caregivers is crucial for providing comprehensive care. This review recommends a structured approach to PD management in Indonesia, incorporating it into chronic disease programs, improving diagnostic tools, and developing caregiver support systems to address the growing PD burden and optimize patient outcomes in resource-limited settings.